Age-Adjusted Associations Between Comorbidity and Outcomes of COVID-19: A Review of the Evidence From the Early Stages of the Pandemic - Mason, Kate E.; Maudsley, Gillian; McHale, Philip; Pennington, Andy; Day, Jennifer; Barr, Ben (Frontiers in Public Health, 2021)
Objectives: People with underlying comorbidities are overrepresented in hospitalised cases of COVID-19, but any relationship between comorbidity and COVID-19 outcomes may be confounded by age. Methods: We conducted a rapid, comprehensive review of the literature (to 14 May 2020), to assess the international evidence on the age-adjusted association between comorbidities and severe COVID-19 progression or death, among hospitalised COVID-19 patients. Results: After screening 1,100 studies we identified 14 eligible for inclusion. Overall, evidence for obesity and cancer increasing risk of severe disease or death was most consistent. Most studies found that at least one of obesity, diabetes mellitus, hypertension, heart disease, cancer, and chronic lung disease was significantly associated with worse outcomes following hospitalisation. Associations were more consistent for mortality than other outcomes. Increasing numbers of comorbidities and obesity both showed a dose-response relationship. Quality and reporting were suboptimal in these rapidly conducted studies, and additional studies are needed using population-based samples. Conclusions: This review summarises for clinicians, policymakers, and academics the most robust evidence to date on this topic, to inform patient management and pandemic planning. COVID-19 will exacerbate existing health inequalities unless actions are taken to reduce pre-existing vulnerabilities and target control measures to protect groups with chronic health conditions.